Metode Ekspositori : Hasil Belajar Siswa Meningkat Pada Materi Persamaan Garis Lurus (Universitas Muhammadiyah Palembang, 2022)
This study aims to describe student learning outcomes in the material of straight line equations through the expository learning model for class VIII in SMP Negeri X and describe students' responses to the expository model in the mathematics learning process for the material on straight-line equations for class VIII in SMP Negeri X. This research is a classroom action research consisting of 2 cycles. The number of subject was 29 students. The data obtained in this study through test results and student observation sheets taken at each cycle. Based on the results of the study, the data obtained in the first cycle the number of students who met the minimum completeness criteria > 75 totaled 21 people with a percentage of 72.91% and 8 students who did not meet the minimum completeness criteria of < 75 with a percentage of 27.09%. In the second cycle, there were 24 students who met the minimum completeness criteria 75 with a percentage of 82.75% and 5 students who did not meet the minimum completeness criteria <75 with a percentage of 17.25%, which means that student learning outcomes in the second cycle have reached the indicators of success. Thus, it can be concluded that learning by using the expository method on the area of straight line equations can improve student learning outcomes for class VIII SMP Negeri X.